(untitled) (Journal of Dissability Studies and Research (JDSR), 2023)
This thesis discusses thematic learning for children with special needs for hearing impairment in State Special School 1 Jambi City. Thematic learning in Special Schools (SLB) in the Deaf class at this school has implemented the 2013 curriculum which is packaged in thematic form. Basically, the curriculum used in SLB is the same as the curriculum in general elementary schools, except that the basic competencies (KD) in SLB are more adapted to the abilities of students. Basic Competencies (KD) for SLB children are more adapted to their disabilities, and each provision has different Basic Competencies (KD). For example, basic competence (KD) in counting is replaced by recognizing numbers or letters of the alphabet. However, there are obstacles for students who transfer from other schools so that teachers find it difficult to continue the learning stage that they must accept. So it requires teachers to graduate from extraordinary education to be able to adapt to these problems. This study uses a qualitative approach. Then the data collection by using the method of observation, interviews, and documentation. The results of the researchers conducted by researchers are as follows: 1) The thematic learning process for children with special needs for hearing impairment in class III at State Special School 1 Jambi City uses SIBI sign language. 2) Constraints or problems faced by the teacher, namely the first students, the second teacher, the third lesson plan (RPP) to the fourth media, the fifth Facilities and Infrastructure. 3) efforts to overcome the obstacles that occur, namely from students. And from the facilities, the school will try to fulfill all the facilities to support the learning process.